PEMETAAN PERSEPSI NASABAH TENTANG LAYANAN, KEPUASAN, PERSEPSI NILAI, DAN KEPERCAYAAN BANK SYARIAH: ANALISIS DESKRIPTIF DAN HEATMAP - Hafidz Ainur Rofi; Jaharuddin Jaharuddin (Taksasila Edukasi Insani, 2026)
This research aims to analyze the influence of service, satisfaction and perceived value on sharia bank customer loyalty by considering the mediating role of trust. The research method uses a quantitative approach with a survey of 174 Islamic bank customers in Indonesia using a 5-point Likert scale questionnaire. Descriptive analysis shows that all variables have an average value above 4.00, indicating positive customer perceptions of service, satisfaction, perceived value and trust. The research results indicate that good service quality, high satisfaction, and positive value perceptions contribute significantly to customer loyalty. Trust is proven to be a mediating variable that strengthens the relationship between these variables. These findings emphasize the importance of Islamic banks to improve service quality, build satisfaction, and create a balanced perception of value in order to strengthen customer trust and loyalty. Keywords : Service, Satisfaction, Perceived Value, Trust, Customer Loyalty, Sharia Bank